2012
DOI: 10.1371/journal.pone.0046319
|View full text |Cite|
|
Sign up to set email alerts
|

2D:4D Asymmetry and Gender Differences in Academic Performance

Abstract: Exposure to prenatal androgens affects both future behavior and life choices. However, there is still relatively limited evidence on its effects on academic performance. Moreover, the predicted effect of exposure to prenatal testosterone (T)–which is inversely correlated with the relative length of the second to fourth finger lengths (2D:4D)–would seem to have ambiguous effects on academic achievement since traits like aggressiveness or risk-taking are not uniformly positive for success in school. We provide t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 16 publications
0
18
0
2
Order By: Relevance
“…Non-monotonicity may be particularly important in case of biological traits, since they are shaped by evolutionary forces toward “optimal” values [10]–[12] and deviations from these values in any direction might matter. Such an argument is supported by Nye et al [13] who find systematic non-monotonic associations between digit ratio and several measures of academic performance.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…Non-monotonicity may be particularly important in case of biological traits, since they are shaped by evolutionary forces toward “optimal” values [10]–[12] and deviations from these values in any direction might matter. Such an argument is supported by Nye et al [13] who find systematic non-monotonic associations between digit ratio and several measures of academic performance.…”
Section: Introductionmentioning
confidence: 81%
“…On the other hand, some studies have already suggested non-monotonic impacts of 2D:4D on some behavioral outcomes (e.g. [13], [40], [51], [52]). …”
Section: Discussionmentioning
confidence: 99%
“…Previous results based on university students provided the first evidence of a non-linear relationship between 2D:4D and academic achievement using samples from Moscow and Manila. They found that there is a quadratic relationship between high T exposure and markers of achievement such as grades or test scores and that the optimum digit ratio for women in our sample is lower (indicating higher prenatal T) than the average with little to no significant correlations for men (Nye, Androuschak, Desierto, Jones, & Yudkevich, 2012). There may be nonlinearities regarding which women are likely to enter or leave occupations when ranked by skill complexity, status, or income.…”
Section: Discussionmentioning
confidence: 63%
“…We noted earlier that in some studies nonlinear associations of 2D:4D and educational outcomes were found (John V C Nye et al 2012;Sánchez et al 2014). To check for other possible non-monotonic associations and predictors we squared the 2D:4D and included them in regressions with multiple controls (see Table A 14- Table A 16).…”
Section: Figure 1 Difference In Means Of Digit Ratios By Education Comentioning
confidence: 91%
“…As argued by Nye et al (John V C Nye et al 2012) and Nye et al (J V C Nye and Orel 2015), because we have good reason to believe that traits such as confidence or risk-taking or other non-cognitive characteristics are likely to have more positive effects in moderation than at the extremes, we should observe that 2D:4D should exhibit some non-linearity in outcomes, which would have weakened their influence and led to inconsistent findings in literature which only considered first order correlations or linear regressions. Some evidence of nonlinear specifications for these relationships came from the studies of Nye et al for 2D:4D and grades/test scores (John V C Nye et al 2012) and for wages (Nye et al 2014) and Neckerman 1989), limiting the ability to successfully continue education after secondary school. Therefore, one can expect positive correlations between male higher 2D:4D and the completed level of education.…”
Section: Introductionmentioning
confidence: 94%